2004
DOI: 10.1111/j.1582-4934.2004.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Dishevelled‐1 in wound healing after acute myocardial infarction: possible involvement in myofibroblast proliferation and migration

Abstract: One of our previous studies indicated that the expression of β‐catenin, which is the key factor of wnt‐frizzled pathway, increased significantly in the ischemic area of the rat heart 7 days after myocardial infarction (MI). Together with the results of other recent studies, we made an assumption that wnt‐frizzled pathway may be involved in the controlled cell proliferation and migration during repair processes after MI. To verify this assumption we tried to investigate the expression of another signal transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Wound healing in myocardial infarct Regulation of β-catenin might be involved [107][108][109] Implicated in myofibroblast migration [104][105][106] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound healing in myocardial infarct Regulation of β-catenin might be involved [107][108][109] Implicated in myofibroblast migration [104][105][106] …”
Section: Discussionmentioning
confidence: 99%
“…In a rat infarct model, Frizzled-2 is expressed in myofibroblasts that migrate into the infarcted area [104]. In addition, Dvl1 was detected in these myofibroblasts [105,106]. Interestingly, it has been reported that Dvl1 knock out mice may experience problems in infarct healing.…”
Section: Wnt Signalling During Tissue Remodelling In the Mature Heartmentioning
confidence: 97%
“…Members of the Wnt/fz signal transduction pathway are involved in cardiomyopathy and myocardial repair after myocardial infarction. 25,26 The role of the Wnt/fz pathway in programmed cell death is a matter of debate. 27,28 In physiological conditions, the level of ␤-catenin is regulated by Wnt signaling, which stabilizes cytosolic ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Wnt signaling during skin wounding prevents formation of epithelial appendages including hair and sweat glands, which results in prominent scarring of the epidermis (Ito et al 2007). Myocardial infarctions in mammals produce a region of scar tissue surrounding the occluded vessels and if Wnt signaling is repressed, the scarring worsens and the result is myocardial rupture (Chen et al 2004).…”
Section: Wnt Signaling Is Necessary For Tissue Regenerationmentioning
confidence: 99%